2016
DOI: 10.22226/2410-3535-2016-2-132-137
|View full text |Cite
|
Sign up to set email alerts
|

The role of phase transitions in the evolution of dispersion particles in chromium bronzes upon the equal channel angular pressing

Abstract: Samples of a diluted dispersion-strengthening alloy of the Cu-Cr-Zr system were processed with a combination of some severe plastic deformation methods. Preliminary, the samples were quenched into water from a pre-melting temperature to create a supersaturated solid solution concentration. In the course of the experiment the average sizes and distribution density of particles with different chemical compositions undergo an evolution that indicates that phase transformations occur even during the cold deformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 3 publications
1
14
0
Order By: Relevance
“…The lattice parameter analysis by X-ray diffraction (XRD) showed that during ECAP processing, the lattice parameter was restored insignificantly (Table 2). The results are in the domain of statistical error, but based on the previous studies of alloys of this class [1,19,21,22], it can be suggested that there is a process of deformation-stimulated decay of the supersaturated SS. The Cu-0.2Cr and Cu-1.1Cr alloys showed almost the same level of lattice restoration during ECAP processing (~0.0006 Å).…”
Section: Research Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…The lattice parameter analysis by X-ray diffraction (XRD) showed that during ECAP processing, the lattice parameter was restored insignificantly (Table 2). The results are in the domain of statistical error, but based on the previous studies of alloys of this class [1,19,21,22], it can be suggested that there is a process of deformation-stimulated decay of the supersaturated SS. The Cu-0.2Cr and Cu-1.1Cr alloys showed almost the same level of lattice restoration during ECAP processing (~0.0006 Å).…”
Section: Research Resultsmentioning
confidence: 85%
“…The particles thus identified by X-ray analysis are chromium. The specimens were subjected to aging at a temperature of 450 • C [10,19,21,22], which is more characteristic for this class of alloys. Aging up to one hour was completed with an increment of 30 min, and further aging up to 5 h was performed with an increment of 1 h. Micro-hardness and electrical conductivity were measured at each increment.…”
Section: Aging Kinetics Of the Cu-02cr And Cu-11cr Alloysmentioning
confidence: 99%
See 3 more Smart Citations